Chronic breathlessness: symptom or syndrome?. Issue 5 (25th May 2017) - Calverley, Peter M.A.
Maybe it's my age. As a young doctor I was keen to understand the mechanisms of disease in the hope that I could repair what had gone wrong. But now I spend more time in reflection on what illness means to the patient and how it affects their lives. There is nothing new in this process, which was beautifully documented in the book A Fortunate Man by the late John Berger about the life and work of John Sassall, a doctor in a rural area of the UK [1]. For most of my career, breathlessness has been the commonest symptom reported by my patients. Despite its ubiquity, we still struggle to understand the mechanisms that underlie this sensation and the way in which it is perceived by our patients. From the doctor's and carer's perspective, breathlessness is, all too often, an invisible symptom [2] but one that can dominate the patient's life either as a source of immediate distress or as a threat that limits their ability to engage with others and retain their independence. Chronic breathlessness needs more attention than it presently receives http://ow.ly/d3oN30aCImf